Association of Cannabis Use during Adolescence, Prefrontal CB1 Receptor Signaling, and Schizophrenia - Caballero, Adriana; Tseng, Kuei Y. (Frontiers in Pharmacology, 2012)
The cannabinoid receptor 1 (CB1R) is the G-protein coupled receptor responsible for the majority of the endocannabinoid signaling in the human brain. It is widely distributed in the limbic system, basal ganglia, and cerebellum, which are areas responsible for cognition, memory, and motor control. Because of this widespread distribution, it is not surprising that drugs that activate CB1R have expected behavioral outcomes consistent with dysregulated signaling from these areas (e.g., memory loss, cognitive deficits, etc). In the context of this review, we present evidence for the role of CB1R signaling in the prefrontal cortex (PFC), an area involved in executive functions, with emphasis on the developmental regulation of CB1R signaling in the acquisition of mature PFC function. We further hypothesize how alterations in CB1R signaling specifically during adolescent maturation might confer liability to psychiatric disorders.